2013
DOI: 10.1175/jamc-d-12-0256.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low-Level Jets on the Nocturnal Urban Heat Island Intensity in Oklahoma City

Abstract: Previous analysis of Oklahoma City (OKC), Oklahoma, temperature data indicated that urban heat islands (UHIs) frequently formed at night and the observed UHI intensity was variable (1°–4°C). The current study focuses on identifying meteorological phenomena that contributed to the variability of nocturnal UHI intensity in OKC during July 2003. Two episodes, one with a strong UHI signature and one with a weak signature, were studied in detail using observations along with simulations with the Weather Research an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 112 publications
7
52
0
7
Order By: Relevance
“…The UHI circulation distributions for the other two STI cases presented by the dotted and dash-dotted lines in Figure 1a are also calculated (figure omitted). The results suggest that a stronger inversion intensity benefits to a stronger circulation cell, which could be confirmed by observational and numerical experiments (e.g., see [23,24]). …”
Section: Resultssupporting
confidence: 73%
“…The UHI circulation distributions for the other two STI cases presented by the dotted and dash-dotted lines in Figure 1a are also calculated (figure omitted). The results suggest that a stronger inversion intensity benefits to a stronger circulation cell, which could be confirmed by observational and numerical experiments (e.g., see [23,24]). …”
Section: Resultssupporting
confidence: 73%
“…Weak easterly synoptic-scale surface winds were observed on 26 June, but no distinct synoptic-scale surface winds were observed on the other days. In contrast to the synoptic-scale surface winds, somewhat strong westerly sea breezes reported that a nighttime peak of ozone concentration appears when low-level jets enhance vertical mixing and hence transport ozone in the residual layer to the surface (Reitebuch et al 2000;Hu et al 2013). This possibility in the present study needs to be investigated using a coupled meteorology-air quality model.…”
Section: Measurement Sites and Weather Synopsismentioning
confidence: 76%
“…In their simulations, WRF produced insufficient wind shear below the jet, which they attributed to the overly diffusive nature of the chosen PBL schemes. They used WRF-ARW version 3.1.1, however, and many of the PBL parameterizations have since received significant modification, particularly the YSU scheme in version 3.4.1 [as examined in Hu et al (2013)]. …”
Section: A Sensitivity Of Wrf Simulations To Ibc and Pbl Choicementioning
confidence: 99%
“…During the summer months, winds aloft accelerate after sunset with remarkable consistency in numerous regions throughout the central plains and Midwest states. These wind accelerations are known as low-level jets (LLJs), and their influence has been noted in many fields of study, such as clear-air turbulence (e.g., Banta et al 2002), convective storm formation (e.g., Means 1952Means , 1954Curtis and Panofsky 1958), forest fire propagation (e.g., Barad 1961), urban pollution transport (e.g., McNider et al 1988;Banta et al 1998;Hu et al 2013), and turbulent transport (e.g., Prabha et al 2007). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation